Glycaemic control and C- reactive protein levels in type 2 diabetes mellitus -how well they co-relate?: a prospective study - Petchiappan, Velammal; Sivakrishna, Nanubala; Manickam, Santni; Menon, Sujaya (International Journal of Research in Medical Sciences, 2019)
Background: Poorly controlled diabetes mellitus as indicated by elevated glycated haemoglobin (HbA1c) levels is associated with increased cardiovascular risk. C–reactive protein (CRP), an important cardiovascular risk factor, is elevated in diabetics with poor glycaemic control than those with good control. The present study assessed the correlation between HbA1c and CRP levels. Methods: A prospective study was conducted in thirty type 2 diabetic patients irrespective of the disease duration and treatment; those with established target organ damage were excluded. HbA1c and hsCRP levels were measured at baseline; sugars were monitored monthly and medications optimised; at the end of six months HbA1c and hsCRP levels were measured. Results: Mean age of the study subjects was 58.7±8.6 years; At the baseline, all had poor glycaemic control (HbA1c >7%); 15 had hsCRP >3 mg/L. At the end of 6 months, 5 achieved good glycaemic control (HbA1c <7%); 10 had hsCRP >3 mg/L. Baseline median hsCRP was 3.33 mg/L (0.68, 15.9) and at the end of 6 months it was 2.08 mg/L (0.48, 9.12). Mean HbA1c at baseline and end line was 10.6±1.55% and 8.43±1.84% respectively. There was significant reduction in both the mean HbA1c and median hsCRP at the end of 6 months (p <0.001). Positive correlation was observed between HbA1c and CRP at baseline (r=0.32, p=0.10). However, this was not observed at the end of 6 months. Conclusions: There is positive correlation between the level of glycaemic control (HbA1c) and CRP levels; Better glycaemic control results in significant reduction in the hsCRP levels.